Antiproliferative Activity of 2,3,6,7-Tetrahydro-1H-benzo[a]quinolizino[1,9-hi]phenoxazin-14(5H)-iminium Chloride Derivatives - Leitão, Maria Inês (2014)
Compounds based on 1,2,3,5,6,7-hexahydropyrido[3,2,1-ij]quinolone, trivially designated as julolidine, have been reported due to their biological interest, namely as inhibitors of the amyloid-β protein self-assembly (which is associated to the pathogenesis of Alzheimer’s disease), as well as colorimetric and fluorometric probes. Taking this in account, in addition to the relevant biological importance of benzophenoxazinium salts such as Nile Blue derivatives, the present work evaluated the influence of the julolidine moiety in antimicrobial activity against Saccharomyces cerevisiae PYCC 4072 of newly synthesised fluorescent 2,3,6,7-tetrahydro-1H-benzo[a]quinolizino[1,9-hi]phenoxazin-14(5H)-iminium chlorides, in comparison with their analogues.